"A Fighter Pilot's Heaven": Finding Cold War Utility in the North African Desert. (21st September 2016) - Heefner, Gretchen
Abstract : During the Cold War, the United States constructed an unprecedented network of military bases around the world. This expansion forced US policymakers to rethink not only their strategic interests around the world, but also the environments they would encompass. Perhaps nowhere was this more obvious than in Libya, where in the late 1940s the US Air Force began building a massive installation on the shores of Tripoli. This is not, however, the now familiar story of how military bases impact ecosystems. Instead I am interested in the ways that US officials in Libya used ideas about this novel environment—the desert—to justify the appropriation of sovereign territory for military facilities. By comparing US and European views on the Libya environment, I argue that the Americans developed a utilitarian view of the desert that enabled ever-more militarization. By the 1960s, large swaths of the Sahara had been converted into testing and practice ranges. Similar to military facilities in the American West, the Air Force hid its Cold War installations away in the desert. So effective was this strategy, in fact, that the existence of these facilities remains difficult to uncover today.